Understanding c-MET signalling in squamous cell carcinoma of the head & neck. (March 2017) - Szturz, P.; Raymond, E.; Abitbol, C.; Albert, S.; de Gramont, A.; Faivre, S.
Highlights: Preclinical research identified c-MET as a promising target for head and neck cancer. c-MET activation mediates important functions in both malignant and stromal cells. Aberrant signalling includes mutations, amplifications, crosstalk, and overexpression. Immunohistochemical c-MET overexpression may have prognostic and predictive value. c-MET inhibition may overcome resistance to EGFR tyrosine kinase inhibitors. Abstract: c-MET is a membrane spanning receptor tyrosine kinase for hepatocyte growth factor (HGF) also termed scatter factor. Transmitting signals from mesenchymal to epithelial cells, the HGF/c-MET axis mediates a range of biological processes that stimulate proliferation, motility, invasiveness, morphogenesis, apoptosis, and angiogenesis. Aberrant c-MET signal transduction favours tumorigenesis with the acquisition of invasive and metastatic phenotypes. Biological functions of c-MET may strongly vary according to microenvironmental changes, which occur at different stages of tumorigenesis and include also HGF/c-MET activation in stromal cells. In this review, we focused on abnormalities in non-nasopharyngeal squamous cell carcinoma of the head & neck. While the prevalence of c-MET mutations and amplifications ranges 0–25%, c-MET upregulation can be found in the majority of squamous head & neck carcinomas. Despite marked heterogeneity in published scoring methods, immunohistochemical overexpression of c-MET has been typically linked to advanced stages and associated with impaired survival and/or resistance to radiotherapy, chemoradiotherapy, and cetuximab. Experimental studies in cell lines and patient-derived xenografts using various c-MET antagonists (both as single-agents and in combination with cytotoxic and epidermal growth factor receptor [EGFR]-directed agents) yielded promising results, albeit benefit in clinical trials remains to be demonstrated. Consequently, selecting more active agents and integrating them effectively in studies, which incorporate predictive biomarkers such as c-MET gene mutations, amplifications, and overexpression, remains challenging. Further investigations should increase emphasis on disentangling the role of tumour-stromal interactions and analyse their potential as modifiers of drug response.